Alcohol use and associated risk factors among female sex workers in low- and middle-income countries: A systematic review and meta-analysis. - Alicja Beksinska; Oda Karlsen; Mitzy Gafos; Tara S Beattie (PLOS Global Public Health)
Due to its widespread use in the sex work industry, female sex workers (FSWs) in low- and middle-income countries (LMICs) are at high risk of harmful alcohol use and associated adverse health outcomes. Factors associated with harmful alcohol use include violence, mental health problems, drug use, sexual risk behaviors and HIV/STIs. To our knowledge, there has been no quantitative synthesis of FSW alcohol use data to date. This systematic review and meta-analysis aims to provide an estimate of the prevalence of harmful alcohol use among FSWs in LMICs and to examine associations with common health and social concerns. The review protocol was registered with PROSPERO, number CRD42021237438. We searched three electronic databases for peer-reviewed, quantitative studies from inception to 24th February 2021. Studies were selected for inclusion that reported any measure of prevalence or incidence of alcohol use among FSWs aged 18 or older from countries defined as LMIC in accordance with the World Bank income groups 2019. The following study designs were included: cross-sectional survey, case-control study, cohort study, case series analysis, or experimental study with baseline measures for alcohol use. Study quality was assessed with the Center for Evidence-Based Management (CEBMa) Critical Appraisal Tool. Pooled prevalence estimates were calculated for (i) any hazardous/harmful/dependent alcohol use, (ii) harmful/dependent alcohol use only, both overall and by region and (iii) daily alcohol use. Meta-analyses examined associations between harmful alcohol use and violence, condom use, HIV/STIs, mental health problems and other drug use. In total, 435 papers were identified. After screening, 99 papers reporting on 87 unique studies with 51,904 participants from 32 LMICs met the inclusion criteria. Study designs included cross-sectional (n = 89), cohort (n = 6) and experimental (n = 4). Overall, 5 scored as high quality, 79 studies scored as moderate and 15 scored as weak quality. Twenty-nine papers reporting on 22 unique studies used validated alcohol use tools including AUDIT, CAGE and WHO CIDI. The pooled prevalence of any hazardous/harmful/dependent alcohol use was 41% (95% CI: 31-51%), and of daily alcohol use was 26% (95% CI: 17-36%). There was variation in harmful alcohol use by global region (Sub-Saharan Africa: 38%; South Asia/Central Asia/ East Asia and Pacific: 47% and Latin America and the Caribbean:44%). Harmful alcohol use was significantly associated with inconsistent condom use (pooled unadjusted RR: 1.65; 95% CI: 1.01-2.67), STIs (pooled unadjusted OR: 1.29; 95% CI 1.15-1.46); and other drug use (pooled unadjusted OR of 2.44; 95% CI 1.24-4.80), but not with HIV, violence or mental health problems. We found a high prevalence of problem alcohol use and daily alcohol use among FSWs in LMICs. Harmful drinking was associated with important HIV risk factors such as inconsistent condom use, STIs and other drug use. Major limitations included heterogeneity in tools and cut-off scores to measure alcohol use and other common risk factors, and a paucity of longitudinal studies. There is an urgent need for tailored interventions for FSWs in LMICs that address alcohol use as well as the associated sex work risk environment.